2019
DOI: 10.1016/j.gie.2018.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of water exchange colonoscopy on endoscopy room efficiency: a systematic review and meta-analysis

Abstract: Based on parameters of procedural time, the impact of WE colonoscopy on endoscopy room turnaround yields an increase in total procedure time of about 2 minutes and is associated with significant improvement in specific patient-centered outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…34 In a meta-analysis comparing water exchange with a combined group of air and CO 2 insufflation, water exchange was also associated with a higher patient willingness to undergo repeat procedures. 35 Recent network meta-analyses comparing air insufflation, CO 2 insufflation, water exchange, and water immersion techniques demonstrated that air insufflation is associated with the highest pain scores and water exchange with the lowest pain scores. 36,37 Beyond colonoscopy technique, the Multisociety Sedation Curriculum for Gastrointestinal Endoscopy 38 provides a standardized approach to training in sedation administration that can help ensure appropriate and safe sedative practices for endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…34 In a meta-analysis comparing water exchange with a combined group of air and CO 2 insufflation, water exchange was also associated with a higher patient willingness to undergo repeat procedures. 35 Recent network meta-analyses comparing air insufflation, CO 2 insufflation, water exchange, and water immersion techniques demonstrated that air insufflation is associated with the highest pain scores and water exchange with the lowest pain scores. 36,37 Beyond colonoscopy technique, the Multisociety Sedation Curriculum for Gastrointestinal Endoscopy 38 provides a standardized approach to training in sedation administration that can help ensure appropriate and safe sedative practices for endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, even more angioectasias were found with the use of CO 2 , in spite of the fact that WE has a magnification effect. Furthermore, the cecal intubation time was lower compared with those that used WE in colonoscopies studies using CO 2 insufflation (12). A difference in the duration of the procedure was found, but this may be related with the lower insertion depth reached with WE.…”
Section: Discussionmentioning
confidence: 81%
“…Due to the high use of propofol at some hospitals, there may be endoscopists who have not performed colonoscopy under moderate sedation at all or for some time who would feel uncomfortable doing so. For these individuals, skills enhancement courses can be beneficial by providing strategies to minimise patient discomfort and improve caecal intubation and adenoma detection rates, such as by teaching torque steering and loop reduction, varying patient positioning to facilitate passage of the colonoscope,22–26 and use of carbon dioxide insufflation27–29 and water infusion techniques 30–32. Further recommendations made by the expert panel for improving patient experience under moderate sedation are provided in table 1.…”
Section: Discussionmentioning
confidence: 99%